Developing a Financial Information System and Using Its Information Pool for Management Decision-Making - Valkauskas, Romualdas; Vareikaitė, Aistė; Kazlauskaitė, Agnė (Buhalterinės apskaitos teorija ir praktika, 2023)
Reliable financial information, which is usually derived from quantitative research, is crucial for management decision-making. However, in order to apply this result appropriately in the management decision-making process, it is important to be able to explain, interpret, and compare it against the established criteria. Therefore, it is appropriate to establish a financial information system within the company and build a suitable pool of information. This article explores the requirements for financial information, the process of establishing the financial information system, the primary indicators of the financial information pool, and the criteria for evaluating them in the context of management decisions. The analysis of the scientific literature has led to identification of six requirements for the quality of financial information and four dimensions of financial information. The interaction among these aspects provides the prerequisites for developing high-quality financial information system. It was also observed that, in order to develop a financial information system, a company must accumulate an appropriate pool of information, prepare its own individual set of indicators, and establish their indicative values. Furthermore, it was noted that different indicators are used at each level of management within the financial information pool.
Keywords: financial information; financial information requirements; financial information system; financial information pool; management decisions